Content Validity and Reliability of Expert Assessment PLP Guide Book Based on Technological Pedagogical and Content Knowledge - Artha Mahindra Diputera; Anita Yus; Peny Husna Handayani; Dwi Septi Anjas Wulan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Research purpose to determine the content validity and reliability of agreement among experts in assessing the Technological Pedagogical and Content Knowledge on Introduction to the school field (PLP) Guidebook. The research method uses a development model. TPACK based handbook tested by 3 experts. Validity analysis was carried out using Aiken's V analysis and Reliability using Interclass Consistency. The results of the study prove that the manual with  v value of 0.95 is declared valid content with high criteria and an ICC value of 0.517 is declared an expert in assessing. The conclusion of this research is that the content is valid and the experts are appropriate in conducting the assessment. Suggestions for the TPACK based PLP guidebook can be used as guidelines for implementing PLP for lecturers, tutors and students.